EMDR a closer look - Allen, Jon G.; Keller, Michael W.; Console, David A.; Guilford Publications, Inc. (New York : Guilford Press, 1999)
(Producer) Several specialists, including Dr. Shapiro, the originator and developer of EMDR, describe the EMDR process.
Keywords: Stress Disorders, Post-Traumatic -- therapy; Imagery (Psychotherapy) -- methods; Desensitization, Psychologic -- methods; Saccades